2020
DOI: 10.1186/s12905-020-00943-5
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and fertility behaviors: a cross-sectional study in Iranian women health care workers

Abstract: Background Fertility, in addition to the biomedical aspect, is phenomena of social, economic and demographic changes. Social network were considered for understanding fertility behaviors and changes in the levels of fertility. This study was conducted to investigate the relationship between social capital and childbirth behaviors in Iranian women employees. Methods This cross-sectional study was conducted in 2017 on 536 women health care workers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…However, this contradict with a study conducted in India where the sterilization uptake was higher in women younger than 30 years old (8).Women belonging to traditional, no religious and other minority religions had more odds sterilization compared to the women from catholic religion this is because believers are conservatives on the earlier church fathers statement condemning the use of contraception in general, ndings of this study is in line with a study conducted in Nigeria saying that tubal ligation was against by many religious beliefs (29). Odds of female sterilization were high in women from rich household wealth quintile compared to their counterparts from poor household wealth quintiles, this is because women from poor household quintile do need more children expecting to get support from their children which is linked with the wealth ow theory of fertility (30). This nding was in line with a study conducted in Zambia revealed that women from richer household use long acting and non-reversible method than women from poor household wealth quintiles (31).…”
Section: Discussionsupporting
confidence: 87%
“…However, this contradict with a study conducted in India where the sterilization uptake was higher in women younger than 30 years old (8).Women belonging to traditional, no religious and other minority religions had more odds sterilization compared to the women from catholic religion this is because believers are conservatives on the earlier church fathers statement condemning the use of contraception in general, ndings of this study is in line with a study conducted in Nigeria saying that tubal ligation was against by many religious beliefs (29). Odds of female sterilization were high in women from rich household wealth quintile compared to their counterparts from poor household wealth quintiles, this is because women from poor household quintile do need more children expecting to get support from their children which is linked with the wealth ow theory of fertility (30). This nding was in line with a study conducted in Zambia revealed that women from richer household use long acting and non-reversible method than women from poor household wealth quintiles (31).…”
Section: Discussionsupporting
confidence: 87%
“…This can be explained by the wealth ow theory of fertility, where women from poorer households may desire more children in hopes of receiving support from them. [32]. This nding was in line with a study conducted in Zambia, which revealed that women from richer households were more likely to use long acting and non-reversible contraception method compared to women from poor households wealth quintiles [33].…”
Section: Discussionsupporting
confidence: 87%
“…Second, young women with high social capital may experience substantial social pressure from other people, such as their partners or parents-in-law, to have a child ( Balbo & Mills, 2011 ; Firouzbakht et al, 2020 ). Social networks, social pressure, and social capital can affect fertility decisions, particularly if there is little institutional support ( Balbo & Mills, 2011 ).…”
Section: Discussionmentioning
confidence: 99%